THE INFLUENCE OF COMPENSATION AND WORK DISCIPLINE ON EMPLOYEE PRODUCTIVITY IN PT. WAILALA TRANS IN BAUBAU CITY - Sitti Nur Ailsya Nabila; Syamsul Rizal; Syarifuddin Sulaiman (International Journal of Economic Research and Financial Accounting, 2024)
This research starts from the framework of thinking that Compensation and Work Discipline greatly influence employee productivity. This research aims to determine the influence of compensation and work discipline on productivity employees PT. Wailala Trans in Baubau City. The population in this study were all employees of PT. Wailala Trans has 34 employees. This type of research uses a quantitative approach. The data sources used are primary data and secondary data, where the primary data comes from observations and documentation at the company PT. Wailala Trans, and secondary data was obtained by distributing questionnaires to 34 employees of the company PT. Wailala Trans. The data analysis technique used is multiple regression data analysis by combining statistical calculations using the Data Analysis Tools program in Windows Excel version 16 and the Statistical Package for the Social Science (SPPS) application version 23. The results of this research show that the compensation variable (X1) has no effect on employee productivity, the work discipline variable (X2) has an effect on employee productivity, meanwhile the compensation and work discipline variables together have a significant and simultaneous effect on the work productivity of employees PT. Wailala Trans, can be seen from the significance value of Sig 0.002 < 0.05, and the Fcount value of 7.560 > Ftable value of 3.304.